Impact of Liquidity on Profitability in Nepalese Commercial Banks (Journal of Management, 2020)
The aim of this paper is to examine the impact of liquidity on profitability in Nepalese commercial banks. Market price, earning per share, net profit margin and return on assets are taken as the indicators of profitability. Deposit-credit ratio, cash reserve ratio and capital adequacy ratio are taken as the indicators of liquidity. This study has tried to determine the association between liquidity and profitability indicators of 27 commercial banks out of 28 commercial banks in Nepal. The cross-sectional secondary data of these banks were used. Descriptive and causal comparative research strategies were applied to analyse the data. Correlation analysis and multiple general linear regression analysis were applied to establish the association. This study has found that there is no statistically significant association between liquidity and profitability indicators in Nepalese commercial banking industry. The data were analysed using statistical software mini tab.